EFFICACY OF GLP-1 RECEPTOR AGONISTS ON GLYCAEMIC CONTROL AND WEIGHT REDUCTION IN TYPE 2 DIABETES MELLITUS: A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS - Nadhira Iriani Djatmiko; Muhamad Luthfi Asyhar; Rifqi Alridjal; Zia Faradila; Fitria Hazmi Sholihah; Brigitta Vania Santoso; Muhammad A'raaf Sirojan Kusuma; Charles Sanjaya (The Indonesian Journal of General Medicine, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) is a metabolic disorder with a rapidly escalating global burden and is closely linked to obesity and cardiovascular disease. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are an incretin-based therapeutic class that simultaneously targets hyperglycaemia and adiposity. This systematic review aimed to evaluate the efficacy of GLP-1 RAs on glycaemic control and weight reduction in T2DM on the basis of randomized controlled trial (RCT) evidence. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligible studies were RCTs in adults with T2DM comparing a GLP-1 RA with placebo or an active comparator and reporting HbA1c and/or body weight outcomes. Risk of bias was assessed using the Cochrane Risk of Bias 2 (RoB 2) tool and certainty of evidence using the GRADE approach. Because of substantial clinical heterogeneity, evidence was synthesised in a structured narrative format rather than pooled quantitatively. Results: Thirty-two RCTs comprising 29,958 participants met the eligibility criteria. Every placebo-controlled comparison demonstrated a statistically and clinically significant reduction in HbA1c, with estimated treatment differences (ETDs) ranging from -0.5% to -1.75% (all p<0.001). Subcutaneous semaglutide produced HbA1c ETDs of up to -1.53% and weight reductions of up to -5.06 kg versus placebo, and was superior to exenatide extended release (ETD -0.62%; -3.78 kg) and to dulaglutide (ETD -0.41%; -3.55 kg). Once-weekly semaglutide 7.2 mg reduced body weight by 13.2% (ETD -9.3%) with an HbA1c ETD of -1.5%. The proportion achieving >=5% weight loss reached 68.8% in STEP 2 (odds ratio 4.88) and yielded an odds ratio of 10.0 in STEP UP T2D. Benefit was consistent across 16 outcome domains, including fasting plasma glucose, waist circumference, systolic blood pressure (ETD up to -5.0 mmHg), insulin requirement (glargine titration difference -13 U/day), and major adverse cardiovascular (HR 0.88; 95% CI 0.79-0.99) and renal (HR 0.85; 95% CI 0.77-0.93) outcomes in REWIND. Hypoglycaemia risk remained low, whereas mild-to-moderate gastrointestinal events were the most frequent adverse events. Twenty-three studies were judged at low risk of bias and nine raised some concerns, chiefly owing to open-label designs. Discussion: The consistency of the direction and magnitude of effect across 32 RCTs spanning diverse background regimens (monotherapy, metformin, sulphonylurea, SGLT-2 inhibitor and basal insulin combinations) supports a robust and reproducible class effect. A clear dose-response relationship, the superiority of semaglutide in head-to-head comparisons, and the accompanying cardiorenal benefit reinforce the position of this class within T2DM treatment algorithms for patients with concomitant obesity. Gastrointestinal tolerability and cost remain the principal implementation considerations, particularly within the Indonesian health-care setting. Conclusion: GLP-1 receptor agonists consistently and significantly improve glycaemic control and reduce body weight in T2DM, with a low risk of hypoglycaemia and additional cardiorenal benefit in high-risk populations. The evidence supports positioning GLP-1 RAs as a preferred option in patients with T2DM and overweight or obesity and elevated cardiovascular risk.